Improving MSME Performance Through Financial Literacy, Behavior, and Fintech Use In Jepara - Nimas; Latifah, Lyna; Nur Aeni, Ida; Isdiati, Erni Harlina; Gunawati , Iva Sofi (JAS (Jurnal Akuntansi Syariah), 2025)
This study aims to examine the influence of financial literacy, financial behavior, and improvisational behavior on the performance of Micro, Small, and Medium Enterprises (MSMEs), with a focus on the mediating role of fintech adoption among furniture-based MSMEs in Jepara Regency. A quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data gathered through structured questionnaires distributed to selected MSME actors. The findings reveal that financial literacy significantly and positively affects MSME performance, both directly and indirectly through the mediation of fintech usage. Fintech adoption emerges as a crucial mediating factor that strengthens the positive relationship between financial literacy and MSME performance. In contrast, financial behavior and improvisational behavior do not exhibit a significant effect on MSME performance, either directly or through fintech adoption. Theoretically, this study contributes to the understanding of how digital financial tools mediate the impact of financial competencies on business outcomes. Practically, the findings suggest the need for targeted interventions to improve financial literacy and encourage fintech utilization among MSMEs, especially within the creative economy sector, to enhance competitiveness and support sustainable performance.